2020
DOI: 10.1016/j.apenergy.2020.114888
|View full text |Cite
|
Sign up to set email alerts
|

Modified auxiliary exergy costing in advanced exergoeconomic analysis applied to a hybrid solar-biomass organic Rankine cycle plant

Abstract: This study concerns advanced exergoeconomic analysis of a hybrid solar-biomass organic Rankine cycle (ORC) cogeneration plant. The hybrid plant had been previously conceived as structural optimization scheme to upgrade thermo-economic performance of a real 630 kW solar-ORC plant which currently runs in Ottana, Italy. The irreversibility rates, investment cost rates and irreversibility cost rates were obtained for each system component, based on thermodynamic balance as well as cost balance and auxiliary equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 46 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…For the avoidable and unavoidable splitting parts, the dominant part was determined to be unavoidable for each system component, which was as low as 80.13% for ammonia-HE and as high as 82.46% for lithium bromide pump one. Oyekale et al [43] applied advanced exergy analysis to a hybrid solar-biomass ORC plant having an organic fluid pump and HEs (condenser and evaporator). Based on the conventional exergy assessment, the exergy efficiencies were computed as almost 80% for the pump, almost 28% for the condenser, and 85% for the evaporator.…”
Section: Exergetic Assessmentmentioning
confidence: 99%
“…For the avoidable and unavoidable splitting parts, the dominant part was determined to be unavoidable for each system component, which was as low as 80.13% for ammonia-HE and as high as 82.46% for lithium bromide pump one. Oyekale et al [43] applied advanced exergy analysis to a hybrid solar-biomass ORC plant having an organic fluid pump and HEs (condenser and evaporator). Based on the conventional exergy assessment, the exergy efficiencies were computed as almost 80% for the pump, almost 28% for the condenser, and 85% for the evaporator.…”
Section: Exergetic Assessmentmentioning
confidence: 99%
“…Two strategies are commonly deployed for mitigating these challenges at system level: hybridization with other renewable energy systems, such as biomass, and inclusion of thermal energy storage (TES) systems. Several theoretical and optimization studies have demonstrated the substantial thermo-economic improvements obtainable by hybridizing CSP systems with biomass [82,[117][118][119][120][121][122][123][124]. Moreover, regarding TES inclusion in CSP systems, the current research space is quite wide, and a short review of current progress is thus provided below following that of electrochemical energy storage.…”
Section: Solar Energymentioning
confidence: 99%
“…The organic Rankine cycle (ORC) is a promising technology in waste heat recovery for power generation or cogeneration [ 7 , 8 , 9 ]. One of the advantages of the ORC over conventional steam cycles is the use of organic fluids with a low boiling point, which makes them more adaptable to systems with low-temperature in the heat source compared to water.…”
Section: Introductionmentioning
confidence: 99%